INTERACTIVE PROGRAMS FOR FITNESS TRAINING WITH WOMEN: ADVANTAGES (Multidisciplinary Journal of Science and Technology, 2024)
This article analyzes the role of modern technologies in the correct implementation of sports exercises and the promotion of a healthy lifestyle. The possibilities of monitoring and optimizing physical activity using interactive applications and smart devices are considered. The article also provides information on the state policy of Uzbekistan aimed at developing a healthy lifestyle and the role of technologies in this process. This study aims to study the possibilities of using technologies in the fields of health care and sports, and highlights practical aspects aimed at popularizing a healthy lifestyle among the population, especially women.